2009
DOI: 10.1515/jpm.2009.100
|View full text |Cite
|
Sign up to set email alerts
|

Effect of exogenous surfactant therapy on levels of pulmonary surfactant proteins A and D in preterm infants with respiratory distress syndrome

Abstract: Objectives: To examine whether exogenous pulmonary surfactants (exPS) substitute for or merely supplement endogenous pulmonary surfactants (enPS) by looking at sequential changes in the surfactant proteins (SP) SP-A and SP-D in alveolar pools. Methods: Fourteen preterm infants with RDS treated with an artificial surfactant were compared to five normalterm infants without RDS who were treated with artificial ventilation at birth. Results: Immediately after birth, SP-A and SP-D were essentially absent in the alv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Exogenous surfactant treatment appears to promote endogenous surfactant production and by 48-72 h SP-A and SP-D levels approximate the levels present in term newborns [12] . However, a study by Beresford and Shaw [13] reported that low levels of SP-D (in contrast to SP-A and SP-B) in the first few days of life were associated with a higher risk of developing neonatal chronic lung disease (CLD), thus there could be a critical window soon after birth in which absence of SP-D sets in train an inflammatory reaction which disturbs surfactant homeostasis in those infants going on to develop CLD.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Exogenous surfactant treatment appears to promote endogenous surfactant production and by 48-72 h SP-A and SP-D levels approximate the levels present in term newborns [12] . However, a study by Beresford and Shaw [13] reported that low levels of SP-D (in contrast to SP-A and SP-B) in the first few days of life were associated with a higher risk of developing neonatal chronic lung disease (CLD), thus there could be a critical window soon after birth in which absence of SP-D sets in train an inflammatory reaction which disturbs surfactant homeostasis in those infants going on to develop CLD.…”
Section: Introductionmentioning
confidence: 78%
“…SP-D is a large, multimeric, hydrophilic protein that belongs to the collectin group of carbohydrate-binding proteins, named for their collagen-like domains combined with globular carbohydrate-binding (lectin) domains, other members of which in humans include SP-A, and mannan/mannose-binding lectin [12] . Collectins are calcium-dependent lectins and multimeric sharing a common subunit structure.…”
Section: Sp-d Structure and Functionmentioning
confidence: 99%
“…It was previously demonstrated that SP-A increases in the blood circulation of patients with acute lung injury/acute respiratory distress syndrome [15][16][17] .…”
Section: Discussionmentioning
confidence: 99%
“…The absence or reduction of surfactant is associated with neonatal respiratory distress syndrome and congenital surfactant deficiency 15,16 . Conversely, there is an increase in pulmonary alveolar proteinosis, which is related to significant respiratory dysfunction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation